(untitled) (Journal of actual problems of jurisprudence, 2018)
This article describesthe activityand the activity ofthe courtthe prosecution and defensein criminal proceedings.Activitycourt, the prosecution and defense, is shown during a matchat the court hearing. Whenthere is no disputebetween the partiesin court, the adversarial principleloses its significance. Activitycourtshallconsist only inan effort toestablish the truth. The premise ofthe adversarialtrialcausedthe active sidewiththe leading role ofthe courtin the process.Courtcreates conditions forcompetitionthe party in controlof lawful behavioractors, evaluates evidenceinvestigatedin terms ofaffordability,reliability ofevidence. Key words: court , the defense , the prosecution , the prosecution , the adversarial parties.